Recent advances of using ionic liquid in lignocellulosic biomass degradation - Financie, R. (Trans Tech Publications Ltd, 2014)
Pretreatment is a very important step for cellulose conversion process. The effectiveness of the lignocellulosic pretreatment process is one of the key factors to a successful conversion of the original low-cost material into biofuels or biomaterials. The best pretreatment method depends on the type of lignocellulosic materials, and its affected by degree of cellulose polymerization and degree of acetylation of hemicelluloses of the lignocellulosic materials are the main factors. Therefore, it is desirable to find and develop the best pretreatment process, which is also friendly for the environment, effective and efficient for lignocellulosic material conversion of cellulose with minimal structural alteration. In this current review, pretreatment of lignocellulosic material using ILs is discussed in order to describe the state of the art of ILs as a pretreatment methodology for cellulose and lignin separation. Review of ILs assisted by other processes is also discussed here and perspectives regarding this topic are given as well. Â© 2014 Trans Tech Publications, Switzerland.